2020
DOI: 10.1021/acsenergylett.0c01449
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Nanocrystal Heterostructures: Synthesis, Optical Properties, and Applications

Abstract: Bringing together two nanostructures of different materials in a single building block can create a new platform where both can share their electronic and optical characteristics. While these have been extensively studied for metal nanoparticles and chalcogenide semiconductor nanocrystals, the literature is limited for perovskite nanocrystals. Because perovskite nanocrystals typically follow a fast formation process and also require a specific environment, their growth on other materials or vice versa indeed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 84 publications
(173 reference statements)
2
148
0
Order By: Relevance
“…The bleach recovery was analyzed using a biexponential kinetic fit 35 and the fitting parameters ( a 1 , τ 1 ) and ( a 2 , τ 2 ) corresponding to fast and slow components are presented in Table S3. † While the fast component varied in the range 18.6–6.6 ps the long component varied in the range of 129.6–71.7 ps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bleach recovery was analyzed using a biexponential kinetic fit 35 and the fitting parameters ( a 1 , τ 1 ) and ( a 2 , τ 2 ) corresponding to fast and slow components are presented in Table S3. † While the fast component varied in the range 18.6–6.6 ps the long component varied in the range of 129.6–71.7 ps.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33] Designing perovskite heterostructures with metal chalcogenide shells can have several distinct advantages: (i) providing stability towards increased polarity of the solvent, (ii) remediating surface defects by directly interacting with the vacancies, and (iii) allowing for type I or quasi-type II band alignment to promote increased charge recombination in the core (increased emission yield) or improved charge separation. [34][35][36] In this context, a CsPbBr 3 -CdS heterostructure offers an attractive means to tune the band energies, as their conduction bands are nearly isoenergetic (E CB of CsPbBr 3 and quantized CdS z À0.8 V versus NHE) [37][38][39] and facilitate charge separation. In addition, cubic CsPbBr 3 nanocrystals have a lattice constant (a) of 5.85 Å (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering of nanocrystal heterostructures based on perovskite platform is a novel concept to achieve optoelectronic materials with synergetically improved characteristics. [ 139 ] Heterostructures made of all‐inorganic PNCs and lead sulfide (PbS) QDs provide a unique opportunity to utilize the strong PL in the NIR from QDs far inside the matrix of the nanosized perovskite material. Zhang et al have recently reported the RT synthesis of heterostructured CsPbX 3 –PbS PNCs with a dual emission.…”
Section: Broadly Tunable Emission Toward Nirmentioning
confidence: 99%
“…From the photocatalytic or photoelectrocatalytic point of view, it is noteworthy that the halide perovskite possesses a suitable band structure for the CO 2 reduction. In recent years, some studies on the CO 2 reduction with halide perovskite driven by visible light have been reported (Bera and Pradhan, 2020 ; Shyamal and Pradhan, 2020 ; Wang H. et al, 2020 ). For the reported work involving the CO 2 reduction using perovskite-based photocatalysts, the detailed reaction conditions have been summarized and listed in Table 4 .…”
Section: Perovskite-based Catalytic System For the Photo-reduction Ofmentioning
confidence: 99%